Prevalence and characteristics of mandibular divergency in class III patients - Nada Esam Tashkandi; Sara Saad Alshanbari; Nasser N Almutairi; Abdullah Ali Al Hawsawi; Abdulaziz Ahmed Abuabah; Abdulelah A Alanazi (Wolters Kluwer Medknow Publications, 2021)
Introduction: The classical skeletal divisions of orthodontic patients are the Angle's classification of Classes I, II, and III and of mandibular inclination into normo-, hypo-, or hyperdivergent. Of these classifications, Class III and hyperdivergent are the least studied. This study aimed to investigate the prevalence and relationship between Class III and hyperdivergency. Materials and Methods: Lateral cephalometric radiographs of Class III patients were collected from Riyadh Elm University and were traced by WebCephTM software and measured for 16 linear and angular measurements to determine anteroposterior, vertical, and dental associations. To determine the anteroposterior relationships, Sella-Nasion to A point Angle, Sella-Nasion to B point Angle, A point to B point Angle, and Wits appraisal were used. Class III status was determined by utilizing (A point to B point Angle <1) and (Wits appraisal <−2.5). The vertical divergency pattern was considered according to normal Frankfort horizontal plane and mandibular plane (FMA) (22°-28°) and SN-GoMe: Sella-Nasion to Mandibular plane (27°-36°) measurements. The dental correlation was considered according to upper incisor to maxillary plane (U1-Mx) and lower incisor to mandibular plane angle. Statistical analysis was performed with SPSS (version 25) software. Results and Conclusions: One hundred and twenty-five Class III patients were included in the final analysis of this study. A significant correlation at 0.650 was discovered between ANB and Wits analyses (<0.001). Subjects data was grouped, based on their mandibular divergency, into hypodivergent, normodivergent, and hyperdivergent. The distribution, regardless of measurement used, was significantly higher in the prevalence of hyperdivergents (FMA 46.4% and SNGoMe 56%) over hypo- and normodivergents. Although FMA and SNGoMe were positively correlated at 0.887, there were significant differences in their classification of divergency with higher levels of hyperdivergency with SNGoMe.